Correlation of Color Doppler with Multidetector CT Angiography Findings in Carotid Artery Stenosis - Živorad N. Savic; Lazar B. Davidovic; Dragan Ž. Sagic; Milan D. Brajovic; Srdjan S. Popovic (The Scientific World Journal)
The aim of this paper was to examine the correlation between the Color Doppler ultrasound (CD-US) and multidetector CT angiography (MDCTA) diagnostic methods, and to define the degree and extent of stenosis in patients with internal carotid artery stenosis. This was a cross-sectional study with a consecutive series of patients. All US examinations were always carried out by the same physician-angiologist, while all CT examinations were always carried out by the same physician-radiologist. Both worked independently from each other. The stenosis area was measured at the narrowest point by NASCET criteria for US/CT. Peak systolic velocity (PSV) over 210 cm/sec and end diastolic velocity (EDV) over 110 cm/sec criteria were applied for stenoses with lumen narrowed over 70%, while PSV under 130 cm/sec and EDV under 100 cm/sec criteria were applied for those with lumen narrowed under 70%. A total of 124 carotid arteries were observed; namely, 89 narrowed and 68 surgically treated. All patients were reviewed by US and then by MDCTA; patients with 70–99% stenosis underwent surgery. The correlation coefficient between stenosis degree measured by US and MDCTA was 0.922; p < 0.01. The average difference between US and MDCTA diagnostic methods was 3% (Z = -1.438, p > 0.05). The US and CT matching level for stenoses from 70 to 99% was very high (κ = 0.778, p < 0.01). In conclusion, there is a highly significant statistical correlation among both diagnostic methods when measuring stenosis degree and extent. US is more dependent on the physician, while MDCTA is more objective and independent from the physician. We think it would be appropriate to undertake an MDCTA exam for those patients who are candidates for carotid endarterectomy.